Delay sensitive aware distributed data fault recognition algorithm for distributed sensor networks - Kirubakaran, J; Prasanna Venkatesan G K D; Sampath, Kumar K; Dhanabal, S; Baskar, K (Peer-to-peer networking and applications, 2020)
In the recent past, DistributedSensor Network (DSN) placed a significant role in diverse application that benefits to transmit the information from one location to another location. During the data transmission procedure, the network exploits numerous characteristics such as energy harvesting, resilience, scalability, Delay, Life time, Throughput and Packet Delivery Ratio (PDR). The effective utilization characteristics benefits to improve the complete information transmission progression. Even though the network transmits the information effectually, the network faces numerous disputes such as network failure, node failure, lifetime issues, Throughput, delay, PDR and power consumption problem. These issues are affecting the entire data or information transmission efficiency. In addition to this, selection of path also generate problems that leads to create the security issues because the wrong path selection affects network lifetime as well chances to access the information by unauthorized access. To address these issues Delay Sensitive Aware Distributed Data fault Recognition algorithm (DSA-DDFRA) is proposed with the major objective is to manage the network lifetime, faults and choosing optimized path while making the information transaction. The algorithm is experimentally validated for optimized parameter such as Error Rate, network lifetime, delay, energy, throughput and PDR.